PREVALENCE, KNOWLEDGE AND AWARENESS OF HEPATITIS C AMONG RESIDENTS OF THREE UNION COUNCILS IN MANSEHRA - Jamil, Muhammad Shahid; Ali, Hammad; Shaheen, Robina; Basit, Abdul (Journal of Ayub Medical College Abbottabad, 2010)
Background: Pakistan is home to approximately 10 million HCV infected people. HCV prevalence is expected to be higher in the earthquake affected area of Tehsil Oghi. The aim of this study was to estimate HCV prevalence in three Union Councils of Tehsil Oghi, i.e., Oghi, Shamdhara and Kathai, and to assess HCV knowledge and awareness in the population. Methods: This is an observational study carried out during June 2010. Blood samples of 648 participants were analysed for the presence of anti HCV antibodies using Immuno-chromatographic method and a knowledge and awareness questionnaire was administered to the participants. Results: 394 (61%) participants were females, while 254 (39%) were males. The overall prevalence of HCV in the study area was recorded as 67 (10.3%). Prevalence among male participants was 30 (11.8%), whereas, that among female participants was 37 (9.4%). Prevalence estimates in Oghi, Shamdhara and Kathai were 10.3%, 11% and 9% respectively. Knowledge and awareness regarding HCV was inadequate among the study population. Conclusions: HCV prevalence in the study area is higher than the overall prevalence in Pakistan. HCV related knowledge and awareness among population in the area is inadequate. There is a need to undertake a large scale population based epidemiological study and to introduce health interventions to control and reverse the spread of HCV in the area and to impart health education and awareness to the masses. Keywords: HCV, Hepatitis C, Prevalence, Knowledge, Hazara